Human Resources in The Technology of Social Health Capitalization - Elena PRELIKOVA; Andrey BESEDIN; Polina KARJAKINA (Communications of International Proceedings, 2021)
Human impact on natural resources is associated with the social nature of life. That is why there is a need to ensure compliance of the state of the natural environment with the nature of the development of social systems. Since the functioning of any society, an organization is based on the human factor, there is an objective need to regulate this process. Human resources are a set of characteristics and qualities of a person, which makes it possible to assess his ability to perform certain activities. Currently, human behavior is largely determined by the nature of the environment in which he lives in. In turn, human activity is accompanied by an increase in man-made pressure on the environment, especially in urban areas. High population density, congestion of cities with industrial enterprises, transport exacerbate the ecological situation extremely. In this regard, for the development and effective functioning of the urban community, it is necessary to have a level of social health of its representatives, sufficient to build a system of interaction with each other and focused on achieving a specific goal. This is facilitated by the capitalization of social health, which presupposes the consolidation of representatives of the local community to solve common problems, first of all, problems related to the improvement of the living environment. The authors of the article have developed a technology for capitalizing on the social health of the urban population, which pays attention to human resources. Distinctive features of this technology are focus on the processes of improving the urban environment, the use of geographic information systems in combination with crowdsourcing technology, the creation of a self-replicating relational network.
Keywords: Social Health; Human Resources; Local Community; The Technology of Social Health Capitalization.